Empowering Students' Creative At The Utilization of Moodle-H5P with Flipped Classroom in Global Warming Learning to Enhance Students' Creative Attitudes - Abidaturrosyidah, Abidaturrosyidah; Nurdiyanti, Nurdiyanti; Jumadi, Jumadi; Aldila, Febri Tia; Ulfa, Siti Maryam (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
Fostering creative attitudes is essential in global warming learning, as it helps students think creatively and critically about complex environmental issues. This study aims to examine the impact of Moodle-based interactive media with H5P in flipped classroom settings on improving students' understanding of global warming in physics. The creative attitude indicators measured in this study include curiosity, imagination, collaboration, perseverance, risk-taking, openness to new experiences, independence and self-confidence in one's ideas, persistence, imagination and appreciation of fantasy, discipline and commitment to tasks, and collaboration and group trust. The research uses a pre-experimental design with a one-group pretest-posttest approach. Data were collected through tests, and analysis was conducted using ANOVA and N-Gain analysis. The findings reveal a significant improvement in students' creative attitude test scores after using Moodle H5P-based learning media, as shown by the ANOVA results. Additionally, the N-Gain analysis indicates that the improvement in students' creative attitudes falls into the moderate category. The use of Moodle H5P-based interactive media in a flipped classroom setting has a significant impact on enhancing students' creative attitudes, especially in understanding global warming. The use of Moodle H5P-based interactive media in a flipped classroom setting has a significant impact on enhancing students' creative attitudes towards understanding physics topics, particularly global warming.